PENDAPATAN DAN EFISIENSI TEKNIS USAHATANI KUBIS DI KECAMATAN SUMBEREJO KABUPATEN TANGGAMUS - Handayani, Titis Aditya; Prasmatiwi, Fembriarti Erry; Nugraha, Adia (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
This study is to compare the income and technical efficiency of cabbage farming grown in wet land and in rainfed land and to analyse factors influencing the efficiency. The survey was conducted in Sumberejo subdistrict of Tanggamus Regency, the center of cabbage production, in January 2019. Respondents wererandomly taken 30farmers who grew cabbagein wet land and 31 who grew cabbage in rainfed land. Data are analyzed quantitatively using income, frontier, andmultiple regression analyses.The results showed that the income of cabbage farming grown in wet land and in rainfed landis different, but they both profitable. There is no difference in the technical efficiency. Factors that influence technical efficiency of cabbage farming grown in wet land and in rainfed land are farming cost (negatively) and farmers’ education level and experience (possitively). The only factor influencing technical efficiency of cabbage farming grown in rainfed land is land size. Key words: cabbage farming, income, technical efficiency